Leading Student Assessment
XII, 304 p.
Keywords: This book presents a new and refreshing look at student assessment from the perspective of leading educational theorists, researchers, and practitioners. The authors call for boundary-breaking assessment that reflects clear understandings of the purposes of assessment, a balance of assessment creativity and realism, the ability to detect solutions for assessment challenges, and the capacity to question and imagine assessment alternatives. The 14 chapters offer school and district educators, policy makers, researchers, and university teacher preparation faculty with a comprehensive, current overview of the state and art of student assessment. Key questions are posed about assessment and critical challenges are presented along with sound evidence-based solutions. Student assessment is analyzed in terms of its relationship with classroom instructional practices and large-scale testing programs. Formative and summative assessments are compared and contrasted. The role of psychological assessment in informing classroom practices is profiled along with the need for student voice in fair assessment practices. Readers will be challenged to consider the ecology of student assessment, that is, the impact of assessment in classrooms and schools through to the macro level of globalized societies. The underpinning values and assumptions of student assessment are highlighted. Finally, a rationale is offered for reconceptualizing and redefining assessment. .